Patient-reported outcomes for the Intergroup Sentinel Mamma study (INSEMA): a randomised trial with persistent impact of axillary surgery on arm and breast symptoms in patients with early breast cancer. (January 2023) - Reimer, Toralf; Stachs, Angrit; Veselinovic, Kristina; Polata, Silke; Müller, Thomas; Kühn, Thorsten; Heil, Jörg; Ataseven, Beyhan; Reitsamer, Roland; Hildebrandt, Guido; Knauer, Michael; Golatta, Michael; et al.
Summary: Background: In clinically node-negative breast cancer patients, the INSEMA trial (NCT02466737 ) assessed the non-inferiority of avoiding sentinel lymph node biopsy (SLNB) or axillary lymph node dissection (ALND). Here we present patient-reported outcomes (PROs) as a secondary endpoint. Methods: PROs were assessed for patients with no axillary surgery, SLNB alone, and ALND. Quality of life (QoL) questionnaire EORTC QLQ-C30 and its breast cancer module (BR23) were used at baseline (pre-surgery) and 1, 3, 6, 12, and 18 months after surgery. The QoL scores were compared using repeated measures mixed models based on the safety set. Findings: Between 2015 and 2019, 5502 patients were recruited for the first randomization, and 5154 were included in the intent-to-treat set (4124 SLNB versus 1030 no SLNB). In the case of one to three macrometastases after SLNB, 485 patients underwent second randomization (242 SLNB alone versus 243 ALND). Questionnaire completion response remained high throughout the trial: over 70% at all time points for the first randomization. There were significant differences for the BRBS (breast symptoms) and BRAS (arm symptoms) scores favoring the no SLNB group in all post-baseline assessments. Patients in the SLNB group showed significantly and clinically relevant higher scores for BRAS (differences in mean values ≥5.0 points at all times), including pain, arm swelling, and impaired mobility in all postoperative visits, with the highest difference at one month after surgery. Scoring of the QLQ-C30 questionnaire revealed no relevant differences between the treatment groups, although some comparisons were statistically significant. Interpretation: This is one of the first randomized trials investigating the omission of SLNB in clinically node-negative patients and the first to report comprehensive QoL data. Patients with no SLNB benefitted regarding arm symptoms/functioning, while no relevant differences in other scales were seen. Funding: Supported by German Cancer Aid (Deutsche Krebshilfe, Bonn, Germany), Grant No. 110580 and Grant No. 70110580 to University Medicine Rostock.